Analysis Of Determinants Of E-Commerce Adoption In Msmes: Business Model Canvas Approach - Iskandar, Deddy; Irwanto, Irwanto; Idris, Iswandi (Jurnal Ekonomi, 2024)
This study explores the factors that influence the adoption of E-Commerce by MSMEs using the Business Model Canvas (BMC) approach as a framework. With a case study on Cit Kana Rasa, an MSME producing Acehnese shrimp paste, this study aims to identify opportunities, challenges, and strategies that can be implemented to increase competitiveness through business digitalization. The methods used include surveys and in-depth interviews, as well as analysis of BMC elements. The results of the study indicate that e-commerce adoption can expand the market, improve operational efficiency, and strengthen customer relationships.